Celah Kejahatan dalam Relasi Pangan-Manusia Studi Kasus Ndrangheta dalam Kejahatan Pangan di Italia - Nadita Anisa Ningrum; Hermini Susiatiningsih; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Food crime in the form of food product fraud especially in fraudulent olive oil commodities frequently occurred in the period 2014 to 2017 in Italy. The estimated profit gained by organized crime groups reaches millions of euros. Italian agriculture has finally become the focus of mafia's Ndrangheta involvement in the food chain. This research is aimed to find out why the Ndrangheta group committed food crime in Italy and to analyzed the Ndrangheta group as transnational organized crime group. The Ndrangheta group in the Italian food crime scheme is puzzling as to why human-food relations bring up the Ndrangheta group to commit food crimes in Italy. In response to this phenomenon, this thesis used the concept of transnational organized crime groups and non-traditional security concepts, with qualitative methods. The results showing that the presence and characteristics of the Ndrangheta group, the socio-economic conditions of the Calabria region and the facilitative system encouraged food crime take place in Italy. Also extreme power of Ndrangheta made them worse to be controlled. Therefore multilateral cooperation is needed in the form of institutions or regimes that can press for the urgency of food crime, pursue strategies in deterring and detecting the existence of organized crime groups.